Esterificação e transesterificação de óleos de macaúba com elevada e baixa acidez catalisadas por resinas de troca iônica - Daniel Bastos de Rezende (2011)
The cost of raw materials, source of triglycerides, has the largest contribution to the final price of biodiesel produced by traditional routes, currently adopted in most industrial-scale processes. That contribution comes from the need to use edible and noble oils, with low acidity, such as soybean oil, due to limitations in current technologies. Other fact that raises costs of biodiesel is the use of homogeneous catalyst, like hydroxides and methoxides, which can not be recovered and reused. In addition, post-treatment steps are necessary to purify the biodiesel to remove the catalyst that remained in solution after the reaction, raising the costs of the final product. Those post-treatment operations generate effluents that must have an appropriate destination. This study innovates in two aspects. The first one, relates to the use of a vegetable oil in focus in the State of Minas Gerais, Brazil, in which the current extractive yield generates a raw material with high acidity and, therefore, not suitable to be used in biodiesel production. The second one evaluates the technical feasibility of using ion exchange resins, cationic type and anionic type, as catalyst for esterification and transesterification reactions with samples of macauba oil (Acrocomia aculeata) with high acidity and low acidity, respectively. The advantages of using ion exchange resins as catalysts is that they can be reused, regenerated and easily removed from the reaction product. As a result of this work, in a sample of oil with an initial acidity of 40.8% were achieved acidity reductions up to 94.7% by using cationic resins as catalyst, demonstrating its potential use in the oil pretreatment step. Furthermore, with anion exchange resins, a conversion of 99.6% was achieved in a two sequential steps of transesterification. In another evaluation with high acidity oil sample, the reaction process in two stages, esterification followed by transesterification, a conversion of 84.5% was obtained. All of these results indicate the considerable potential for the use of ion exchange resins as catalysts in biodiesel production.